DEVELOPMENT OF VIDEO MULTIMEDIA “LET'S LEARN THE MEASUREMENT OF TIME, WEIGHT AND LENGTH” IN ELEMENTARY SCHOOL - Putri, Lia Sofia; Rarasati, Ida Putri (Transpublika Publisher, 2023)
The development of instructional media is essential for educators to convey abstract learning content effectively. Multimedia offers a concrete visualization of abstract concepts. This study aims to create an efficient and practical multimedia-based instructional media. The research subjects were third-grade elementary school students. Employing a modified Research and Development (R&D) design, the study utilized questionnaires and interviews for data collection. The research encompassed phases of problem analysis, data collection, product design, design validation, design revision, and product testing. Multimedia was validated by media experts, subject matter experts, and language experts. The obtained scores from media experts were 85.57%, subject matter experts scored 83%, and language experts scored 93.27%. This research contributes to the creation of effective and practical multimedia-based instructional media.